Carbon life cycle assessment of shelterbelts in Saskatchewan, Canada. (1st November 2021) - Rudd, Lindsey; Kulshreshtha, Suren; Belcher, Ken; Amichev, Beyhan
Abstract: Shelterbelts are rows of trees planted around farmyards and field for protection against soil erosion, promotion of biodiversity and wildlife habitat. Additionally, to carbon sequestration through growth in tree biomass and carbon sinks in agricultural soil. In recent years, removal of shelterbelts has become more common, as crop land is preferred under higher crop prices, resulting in increased GHG emissions and decreases in carbon sinks. It is likely that landowners are making decisions without the knowledge of carbon sequestered by these trees. In this study, the level of carbon sequestration for the six common shelterbelt tree species found in Saskatchewan (hybrid poplar, green ash, Manitoba maple, Scots pine, white spruce, and caragana) was estimated using a carbon - life cycle analysis method. Net amount of carbon sequestered was estimated for five sequestration/emission stages – 1) seedling production, 2) transportation of seedlings to farm, 3) planting, 4) maintenance, and 5) growth of shelterbelts on farm. Since some landowners are removing shelterbelts, a removal stage was also included. During removal of shelterbelts, CO2 emissions were produced through: (i) physical process of removing the trees and subsequent burning of the wood; and (ii) loss of soil carbon after the removal over a long period of time. The functional unit for the analysis was one linear kilometer of shelterbelt, the normal structure of shelterbelts on agricultural land. All emissions/sequestration levels were measured as carbon dioxide (CO2 ) by multiplying the molecular weight of carbon dioxide to that of carbon (44/12). Other than the growth stage of shelterbelts, all other stages contributed net greenhouse gas emissions, which offset by carbon sequestration during tree growth. Hybrid poplar is a rapidly growing tree and sequesters the most carbon of the six species in all soil zones. A one km long hybrid poplar shelterbelt sequestered upwards of 1923 t CO2 by age 60 years in the Brown soil zone, compared to 2086 t CO2 over the same period in the Black soil zone. In comparison, in the Brown soil zone, Manitoba maple and white spruce sequestered 756 and 732 t CO2, respectively over the same period. If a landowner decides to remove a 60-year-old shelterbelt, 1205 t CO2 is lost within a short period after removal, whereas 718 t of remaining CO2 is retained as dead organic matter, which is slowly released over a period. Although field shelterbelts may emit greenhouse gases in the earlier stages of development, overall, they are net sinks of carbon and can therefore play a significant role in Canada's plan to reduce GHG emissions from agriculture. Highlights: Six common shelterbelt species investigated (hybrid poplar, green ash, Manitoba maple, Scots pine, white spruce, and caragana). A carbon life cycle analysis was undertaken for three soil zones of Saskatchewan. Five sequestration/emission stages were included: (1) seedling production, (2) transportation, (3) planting, (4) maintenance, and (5) growth. Other than the growth of shelterbelts, all other stages led to net carbon dioxide emissions. Hybrid poplar, followed by Manitoba maple and white spruce, were found to be the species with most sequestered carbon.